Potential but limited redundant roles of MtPIN4, MtPIN5 and MtPIN10/SLM1 in the development of Medicago truncatula - Zhou, Chuanen (Landes Bioscience, 2011)
Auxin polar transport is crucial in regulating plant growth and patterning. As auxin efflux carriers, the PIN FORMED (PIN) proteins are responsible for transportation of auxin out of the cell. There are eight and ten PIN members in Arabidopsis (AtPIN) and Medicago truncatula (MtPIN), respectively. Compared with MtPIN10/SMOOTH LEAF MARGIN1 (SLM1), MtPIN4 exhibits a closer relationship with AtPIN1 based phylogenetic analysis. In addition, the gene structure and distribution of transmembrane segments of MtPIN4, MtPIN5 and MtPIN10/SLM1 are similar, implying possible redundant roles among them. However, analysis using Gene Expression Atlas revealed different expression patterns among MtPIN4, MtPIN5 and MtPIN10/SLM1. Loss of function of MtPIN10/SLM1 in M. truncatula resulted in pleiotropic phenotypes in different organs, which are similar with the defects in the pin1 mutant of Arabidopsis, suggesting that the MtPIN10/SLM1 is a putative ortholog of AtPIN1. MtPIN4, MtPIN5 and MtPIN10/SLM1 may have limited redundant functions in the development of M. truncatula. The creation of double and triple mutants will help to elucidate their potential roles in auxin transport and plant development.